Assessing the Legal Certainty of the Sharia Capital Market in Indonesia: Between Normative Concepts and Practical Reality - Cucu Nurjanah; Anwar Sudirja; Rachmawati Puspitasari (Eastasouth Institute, 2026)
The Islamic capital market is part of the Islamic financial system that serves as an investment platform in accordance with Sharia principles. This article discusses the fundamental concepts of the Islamic capital market, the regulations governing it in Indonesia, and its implementation in economic practices. The locus of this research is the Islamic capital market in Indonesia, particularly in the regulatory framework, investment instruments, and implementation of Sharia principles. The study highlights key regulations, such as the Capital Market Law, regulations issued by the Financial Services Authority (OJK), and fatwas from the National Sharia Board of the Indonesian Ulema Council (DSN-MUI), which serve as guidelines for the operation of the Islamic capital market. Additionally, this research analyzes available investment instruments in the Islamic capital market, including Sharia stocks, sukuk, and Sharia mutual funds. Using a normative research method through literature studies, this article finds that the development of the Islamic capital market in Indonesia has experienced significant growth, supported by increasingly robust regulations and rising investor awareness of Sharia-based investments. However, challenges remain in the implementation of the Islamic capital market, such as limited financial literacy in Sharia finance and a lack of innovative instruments. Therefore, strengthening regulations and educating the public are crucial factors in optimizing the role of the Islamic capital market in the national economy.